Kepuasan Pengunjung Taman Impian Jaya Ancol yang Di Pengaruhi Daya Tarik Wisata, Life Style Dengan Persepsi Harga Sebagai Variabel Mediasi - Nur Isnania, Fatra; Aris Budiono (MAMEN: Jurnal Manajemen, 2022)
This study aimed to determine the effect of tourist attraction and lifestyle on visitor satisfaction through price perception at Taman Impian Jaya Ancol Jakarta. Data was obtained in April 2022 with as many as 100 respondents with 20 respondents for validity and reliability tests and 80 respondents for path analysis tests, sampling using the Roscoe technique, all of whom were visitors to Taman Impian Jaya Ancol. The path analysis technique shows the direct and indirect path as the dependent variable to the independent variable. This study resulted in several conclusions as follows: tourist attraction has a significant effect on price perception, lifestyle has a significant impact on price perception, tourist attraction has no considerable effect on visitor satisfaction, lifestyle has a substantial impact on visitor satisfaction, price perception has a significant effect on visitor satisfaction, tourist attraction has no impact on visitor satisfaction through price perception, lifestyle does not affect visitor satisfaction through price perception